PRECOCIOUS PUBERTY AMONG GIRLS IN SULAIMANI: CAUSES AND ANTHROPOMETRIC FEATURES - Albassam, Hayder Ghalib; Tayib, Tara Hussein; Hasan, Adnan Mohammed (Journal of Sulaimani Medical College, 2019)
Background Girls who reach puberty early can fail to reach their expected final height. In addition, they are prone to negative psychological behavior and there is an association with the future development of other negative health outcomes such as diabetes and heart disease. Objectives To determine the causes of female patients with precocious puberty and address some anthropometric features of the studied patients. Patients and Methods Data of 63 female patients who presented with signs and symptoms of puberty before the age of 8 years between the years 2012 and 2018 were collected and analyzed to find the percentages of certain etiologies and features and compare them to similar studies conducted in other countries. Results Central idiopathic precocious puberty (CIPP) was the major diagnosis for the cases and other causes were identified. Causes from the most prevalent to the least prevalent include premature adrenarche, premature thelarche, functional ovarian cysts, and brain tumors. The study also showed a significant relationship between the body weight represented by Body Mass Index (BMI) at the time of presentation and the incidence of central idiopathic PP. Moreover, patients with premature adrenarche also had significantly higher BMI than their peers with normal puberty timing. In addition, the mean height at the time of diagnosis of the PP patients, in general, was significantly higher than their peers with a normal onset of puberty. Furthermore, the heights of the patients with CIPP is significantly negatively correlated with the age at which symptoms of puberty appeared. Finally, the bone ages of girls with PP with the different etiologies were significantly higher than the chronological age. Conclusion Precocious puberty in girls is an important condition in Sulaimani and it has different etiologies. Central idiopathic precocious puberty is the most common etiology. Girls with PP tend to be significantly taller at the time of the diagnosis, have heavier weights and have more advanced bone ages than the normal population.
Keywords: Precocious puberty; Premature thelarche; Premature adrenarche; Bone age